L2 learners’ receptive and productive knowledge of phrasal verbs - Kamarudin, Rafidah; Abdul Majid, Faizah; Md. Zamin, Ainul Azmin; Mat Daud, Nor Shirah (Australian International Academic Centre PTY.LTD., 2019)
Phrasal verbs (PVs) are very common in English, indicating their usefulness in everyday settings. However, it was reported that language learners generally have great difficulties in understanding and using this linguistic form. This study investigated Malaysian learners’ receptive and productive knowledge of PVs, and some possible factors which may contribute to their difficulties in understanding and using this language feature. A set of PVs test was developed and distributed to 480 secondary school learners in Malaysia to identify their receptive and productive knowledge with respect to PVs. Real data from the English of Malaysian School Students (EMAS) Corpus was used to examine the actual use of PVs by Malaysian learners. Results of the PVs test indicated that in general, Malaysian learners had an average level of knowledge of PVs. Analysis of the EMAS corpus revealed that they faced a lot of problems in the production of PVs. Some possible factors are highlighted which may contribute to such difficulties.